Digital economy and ecological performance: Evidence from a spatial panel data in China - Xiaomeng Shen; Haoxiang Zhao; Jingyue Yu; Zhicheng Wan; Taiyi He; Jiawei Liu (Frontiers in Environmental Science, 2022)
The rapid development of information and communication technologies has brought the concept of digital economy into the limelight. Data elements have played a more important role in economic production. As an environmentally friendly economic model, the data factor-driven economy, compared to the traditional one, has low energy consumption and less pollution emissions. Hence, the effect of digital economy development on ecological performance is worth exploring. We measured the digital economy index and the ecological performance index for 30 provinces in China. Furthermore, the relationship between the two was analyzed with the help of a dynamic spatial Durbin model. The results showed the following: 1) closely related to the regional economic foundation, the development level of the digital economy showed obvious spatial characteristics that were high in the eastern region and low in the western region in China. 2) Over time, the pattern of ecological performance in China has changed markedly, showing a high level in the south and a low level in the north. 3) The digital economy showed a significant promoting effect on ecological performance, with a strong externality in space that could have a spillover effect on the surrounding areas. 4) The effect of the digital economy on ecological performance had a significant positive effect, although it lagged behind over time. In addition, the effect has regional heterogeneity and was more obvious in developed regions. Based on these findings, we recommend that the role of ICT in economic activity be strengthened in some developed regions. However, in some developing regions, a balance needs to be struck between digitalization and environmental benefits. At the same time, developed regions should be encouraged to realize economic collaboration with developing regions, with the help of data elements in an effort to narrow the regional gap.